Severance Pay Programs around the World : History, Rationale, Status, and Reforms - Holzmann, Robert (World Bank, Washington, DC, 2017)
The paper examines severance pay programs around the world by providing the first ever overview of existing programs, examining their historic development, assessing their economic rationale and describing current reform attempts. While a significant part of the paper is devoted to a comprehensive 183 cross country review of existing severance arrangements and their characteristics, the paper goes beyond a mere description. It develops and empirically tests three hypotheses about the economic rationale of the program, namely severance pay being: (i) a primitive income protection program, (ii) an efficiency enhancing human resource instrument, and (iii) a job protection instrument. The paper also reviews the recent reforms of Austria, Chile, Italy, and Korea.